2007
DOI: 10.1097/qad.0b013e3280d5a786
|View full text |Cite
|
Sign up to set email alerts
|

In utero nucleoside reverse transcriptase inhibitor exposure and signs of possible mitochondrial dysfunction in HIV-uninfected children

Abstract: Our study suggests that first exposure to 3TC or ZDV/3TC in the third trimester may be associated with the occurrence of possible MD. Further studies that rigorously assess MD and better control confounding are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 27 publications
1
102
1
1
Order By: Relevance
“…While some studies have reported less than 1% prevalence, 4,5,19 most studies have reported prevalence rates of 1%-3%. 6,8,14,15,20 Although our prevalence is higher, this may be because the NISDI study was designed specifically to detect both adverse and serious adverse events among HEU infants, and thus, the neurologic outcomes included were much broader (including head circumference to ascertain microcephaly) compared to previous studies that looked only at MD as an outcome. In fact, excluding microcephaly, our observed prevalence of other specific neurologic diagnoses was only 2.4%, which is more in line with the 1%-3% prevalence frequently reported.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…While some studies have reported less than 1% prevalence, 4,5,19 most studies have reported prevalence rates of 1%-3%. 6,8,14,15,20 Although our prevalence is higher, this may be because the NISDI study was designed specifically to detect both adverse and serious adverse events among HEU infants, and thus, the neurologic outcomes included were much broader (including head circumference to ascertain microcephaly) compared to previous studies that looked only at MD as an outcome. In fact, excluding microcephaly, our observed prevalence of other specific neurologic diagnoses was only 2.4%, which is more in line with the 1%-3% prevalence frequently reported.…”
Section: Discussionmentioning
confidence: 63%
“…The findings of this investigation are consistent with those of previous studies that found no association between in utero ARV exposure and neurologic outcomes, such as MD, [10][11][12][13]20,21 neurologic events, 14,21 and congenital abnormalities 15 among HEU infants. However, there are other studies that did find associations between in utero ARV exposure and MD, 4,8 hyperlactatemia, 22 febrile seizures, 6 and neurologic dysfunction. 7 Our analysis examined differences by specific ARV drug among all cART-exposed infants, while other studies compared cART-exposed infants to those unexposed.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Mitochondrial dysfunction should be considered in children with perinatal ARV exposure who present with severe clinical findings of unknown etiology, particularly neurologic findings. [67][68][69][70][71][72][73][74] Information regarding in utero and/or neonatal ARV exposure should be part of the ongoing permanent medical chart of the child, particularly for uninfected children. Children with in utero ARV exposure who develop significant organ-system abnormalities of unknown etiology, particularly of the nervous system or heart, should be evaluated for potential mitochondrial dysfunction.…”
Section: Long-term Toxicitymentioning
confidence: 99%